2007
DOI: 10.1103/physrevb.76.125204
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Fe in Si and its interactions with hydrogen and shallow dopants

Abstract: The properties of interstitial iron in crystalline silicon and its interactions with hydrogen, shallow acceptors ͑B, Al, Ga, In, and Tl͒, and shallow donors ͑P and As͒ are calculated from first-principles in periodic supercells. The interactions between the ͕Fe,B͖ pair and interstitial hydrogen are also examined. The configurations, electronic structures, and binding energies are predicted. The relative stability of the trigonal and orthorhombic structures of the Fe-acceptor pairs are calculated as a function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 109 publications
7
44
0
Order By: Relevance
“…This finding, however, does not contradict the reported possible Fe-H pairs in the literature, [21][22][23][24] which were shown to anneal out at temperatures above 175 C, 22,23 agreeing with the theoretical calculations of the low binding energy of Fe-H pairs. 24 Estreicher et al 35 conjectured the formation of substitutional iron (Fe s ) in Si via the reaction of interstitial iron (Fe i ) with a pre-existing vacancy. According to Estreicher et al's predictions, Fe s has an acceptor energy level in the upper half of the bandgap.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This finding, however, does not contradict the reported possible Fe-H pairs in the literature, [21][22][23][24] which were shown to anneal out at temperatures above 175 C, 22,23 agreeing with the theoretical calculations of the low binding energy of Fe-H pairs. 24 Estreicher et al 35 conjectured the formation of substitutional iron (Fe s ) in Si via the reaction of interstitial iron (Fe i ) with a pre-existing vacancy. According to Estreicher et al's predictions, Fe s has an acceptor energy level in the upper half of the bandgap.…”
Section: Discussionsupporting
confidence: 74%
“…[13][14][15][16][17] This hypothesis was based on the reports that showed that the recombination activity and the concentration of interstitial iron in silicon were reduced after hydrogen incorporation, via exposure to hydrogen plasma, [18][19][20] hydrogen ion implantation, 21 wet chemical etching, 22 or deposition of PECVD silicon nitride films. 23 While there have been reports of the detection of new defect levels assigned to possible Fe-H complexes, [21][22][23] from theoretical calculations the binding energy of Fe-H pairs was found to be weak, 24 indicating the unlikelihood of the Fe-H pairs withstanding the relatively high temperatures used for firing. Others have suggested that the reduction was due to the accelerated precipitation of iron driven by hydrogenenhanced iron diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…B − , is a well-known phenomenon [1][2][3]22,23,40 . In the next subsections we discuss each type of observed lattice site that we unambiguously identified, comparing with ab initio calculations 21,40,41 and Mössbauer spectroscopy [42][43][44][45] studies from literature.…”
Section: Discussionmentioning
confidence: 99%
“…The Coulomb repulsion energy between Fe − i and B − s is about 0.52 eV 2 , which is somewhat smaller than the reported diffusion barrier energy (0.67 eV) for Fe + i in silicon. 2,6 However, the migration barrier from the 1 st to 2 nd neighbors of B is (0.9-1.0) eV and (0.78-0.90) eV for Fe 0 i and Fe + i , respectively. 18,26 Even though there is no data available about the migration energy for Fe − i , it should be larger than that of Fe 0 i , due to its larger radius.…”
mentioning
confidence: 99%
“…FeB is a strong recombination center with a donor level 0.1 eV above the valence band edge E v, and a deep acceptor level (0.26 ± 0.03) eV below the conduction band edge E c . 2,6,7 The latter state is the dominant recombination center. 8,9 Since Fe i and FeB have different carrier recombination properties, either the dissociation or the association of FeB can be monitored by lifetime measurements.…”
mentioning
confidence: 99%